Importance and uses of underutilized edible fruit Ankol - Kumar, Ajay; Gupta, A K (Indian Horticulture, 2020)
Alangium salvifolium (Linn. F.) Wang. is commonly known ankol, belongs to family Alangiaceae. A. Salvifolium is an underutilized edible, small deciduous shrub that can grow up to a height of 10 m. It is mostly found in wild form in forest and in dry region of plains and also in low hills. It has high amount of carbohydrates, of vitamin C, E, potassium and sodium. It also has anthocyanin and flavonoid pigments. The leaves stem and root are a rich source of alkaloid, tannin and phenols. Stem and bark have antifungal and antiferility activity, respectively.